A memory assistant for the elderly - Costa, Ângelo (2009)
In the present-day the ageing population is not receiving the proper at- tention and care they need, because there aren’t enough healthcare providers to ev- eryone. As the elderly relatives have less time to take care of them the healthcare centers are without any doubt insufficient for all, for these reasons there is an extra pressure or demand on the healthcare sector. Focusing on the elderly care, as the human capacity of memorizing events decreases over time, it is intended to promote an active ageing lifestyle for the elderly, where memory assistance tools are vital component. In this paper, it is presented an scheduler which takes charge of the day-to-day tasks and the user agenda.